The landscape of drug resistant Tuberculosis in South-East Asia (SEA) region: a burden of disease and challenges in detection - Ferdous, Shehreen (Brac University, 2022)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Microbiology, 2021.